NUCINELLA ALIBRANDI (CONTI, 1864) AND N. SEGUENZAE (DALL, 1898),THE LAST EUROPEAN NUCINELLIDS (BIVALVIA, PROTOBRANCHIA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The revision of the genus Nucinella Wood, 1851 from the Italian Pleistocene led to the identification of two species, Nucinella alibrandi (Conti, 1864) and N. seguenzae (Dall, 1898). The former is from the continental shelf deposit of Monte Mario (Rome), the latter from upper slope deposits in Southern Italy (Calabria and Messina). The two species are very similar to each other and differ mainly in the anterior features of hinge. The peculiar hinge of Nucinella is examined in detail and its ontogenetic changes are reported. The Tertiary to Quaternary palaeobiogeographic history of Nucinella in the European area proves the Tethyan origins of this genus. Since the closure of the seaway to the Indo-Pacific in the Early Miocene, Nucinella survived in the European waters as a Tethyan relict until the Plio-Pleistocene, when cooling caused its definitive disappearance. N. alibrandi and N. seguenzae are the last representatives of the genus in the European waters.